Nucleus Reuniens Is Required for Encoding and Retrieving Precise, Hippocampal-Dependent Contextual Fear Memories in Rats - Ramanathan, Karthik R. (J Neurosci, 2018)
The nucleus reuniens (RE) is a ventral midline thalamic nucleus that interconnects the medial prefrontal cortex (mPFC) and hippocampus (HPC). Considerable data indicate that HPC–mPFC circuits are involved in contextual and spatial memory; however, it is not clear whether the RE mediates the acquisition or retrieval of these memories. To examine this question, we inactivated the RE with muscimol before either the acquisition or retrieval of pavlovian fear conditioning in rats; freezing served as the index of fear. We found that RE inactivation before conditioning impaired the acquisition of contextual freezing, whereas inactivation of the RE before retrieval testing increased the generalization of freezing to a novel context; inactivation of the RE did not affect either the acquisition or expression of auditory fear conditioning. Interestingly, contextual conditioning impairments were absent when retrieval testing was also conducted after RE inactivation. Contextual memories acquired under RE inactivation were hippocampal independent, insofar as contextual freezing in rats conditioned under RE inactivation was insensitive to intrahippocampal infusions of the NMDA receptor antagonist aminophosphonovalerate. Together, these data reveal that the RE supports hippocampal-dependent encoding of precise contextual memories that allow discrimination of dangerous contexts from safe contexts. When the RE is inactive, however, alternate neural systems acquire an impoverished contextual memory that is expressed only when the RE is off-line. SIGNIFICANCE STATEMENT The midline thalamic nucleus reuniens (RE) coordinates communication between the hippocampus and medial prefrontal cortex, brain areas that are critical for contextual and spatial memory. Here we show that temporary pharmacological inactivation of RE impairs the acquisition and precision of contextual fear memories after pavlovian fear conditioning in rats. However, inactivating the RE before retrieval testing restored contextual memory in rats conditioned after RE inactivation. Critically, we show that imprecise contextual memories acquired under RE inactivation are learned independently of the hippocampus. These data reveal that the RE is required for hippocampal-dependent encoding of precise contextual memories to support the discrimination of safe and dangerous contexts.